USING DICTIONARY GRAPHICS TO CREATE A THESAURUS OF AGRICULTURAL TERMS (Academicia Globe: Inderscience Research, 2024)
This scientific article reveals the problems and solutions of using dictionary graphics in creating a thesaurus of agricultural terms. Using the technology of creating a thesaurus in the dictionary, which includes the analysis of agricultural terms, applying it to the teaching process is one of the important factors of quality education. Our article talks about the research done in creating a thesaurus of agricultural terms.